Unmasking Hidden Deficits: Language, Cognitive, and Mathematical Challenges in Children with Allergic Rhinitis - Savaş, Merve; Emrah, Göksu İrem; Dilek, Fatih; Kahraman Beğen, Senanur (The European Research Journal, 2026)
Objective: Children with allergic rhinitis are known to exhibit atypical developmental patterns and may face difficulties in language, speech, cognitive, and academic skills. This study aims to compare children newly diagnosed with allergic rhinitis (ages 6-9) with their typically developing peers in terms of language development, cognitive performance, and mathematical skills.Methods: A total of 70 participants were included in the study, comprising 35 children with newly diagnosed allergic rhinitis and 35 healthy controls. Following the collection of sociodemographic data, participants were assessed using the Test of Language Development Primary-Fourth Edition: Turkish Version (TOLDP-4:T), the Wechsler Intelligence Scale for Children-Revised (WISC-R), and a set of age-appropriate non-routine mathematical problems.Results: According to the TOLDP-4:T results, children in the allergic rhinitis group demonstrated below-average performance in listening, organizing, grammar, and over all language skills, whereas their healthy peers performed at an average level. In the WISC-R assessment, the allergic rhinitis group had significantly lower mean scores compared to the control group. While a significant correlation between verbal IQ scoress and mathematical performance was initially found, this relationship was no longer statistically significant after applying the Bonferroni correction.Conclusion: Allergic rhinitis appears to have a negative impact on children’s language development, cognitive abilities, and mathematical performance. These findings highlight the importance of early identification and intervention for children with allergic rhinitis to support their developmental outcomes.